1998
DOI: 10.1111/j.1741-6612.1998.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiving of Older People with Dementing Illnesses in Nursing Homes: a Lifeline of Special Care

Abstract: Objective: Explore the meaning of the care given by family caregivers to family members with a dementing illness after their placement in a nursing home. Method: A constructivist approach, informed by symbolic interactionism, and using grounded theory methods, served as the theoretical and analytical underpinnings of this study. In all, 14 family caregivers (predominantly daughters caring for mothers) were interviewed. Results: There is a dual meaning inherent in family caregiving activities in this context. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…For example, in a comparative study of family caregivers for a relative with dementia at home and those who had placed their relative in a nursing home, Stephens, Kinney, and Ogrocki (1991) found that caregivers visited their institutionalized relatives, on average, 2.9 days per week. Other research demonstrates that a majority of family caregivers visit relatives living in nursing homes at least weekly (Bitzan & Kruzich, 1990;Fleming, 1998;Hook, Sobal, & Oak, 1982). Some studies find length of residence is negatively correlated with the frequency of visits (e.g., Bitzan & Kruzich, 1990;Green & Monahan, 1982;Hook et al, 1982), but other studies find no association (e.g., Minichiello, 1989).…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…For example, in a comparative study of family caregivers for a relative with dementia at home and those who had placed their relative in a nursing home, Stephens, Kinney, and Ogrocki (1991) found that caregivers visited their institutionalized relatives, on average, 2.9 days per week. Other research demonstrates that a majority of family caregivers visit relatives living in nursing homes at least weekly (Bitzan & Kruzich, 1990;Fleming, 1998;Hook, Sobal, & Oak, 1982). Some studies find length of residence is negatively correlated with the frequency of visits (e.g., Bitzan & Kruzich, 1990;Green & Monahan, 1982;Hook et al, 1982), but other studies find no association (e.g., Minichiello, 1989).…”
mentioning
confidence: 97%
“…Similarly, continuing family involvement seems to benefit the quality of life of institutionalized elderly persons, either by improving psychological functioning (Green & Monahan, 1982), or by assuring the quality of institutional care (Fleming, 1998). For example, Green and Monahan (1982) found that elderly persons with frequent family visits had lower levels of psychosocial impairment, suggesting that these visits had a significant therapeutic influence.…”
mentioning
confidence: 99%
See 3 more Smart Citations